FACTORS CONTRIBUTING TO MATERNAL MORTALITY IN TASIKMALAYA CITY - Dewi Andariya Ningsih; Wiryawan Permadi; Dinan S. Bratakoesoema; Hadi Susiarno; Henni Djuhaeni; Polar Silumi (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
Maternal deaths reflect the risks faced by mothers during pregnancy, childbirth, and postpartum were affected by maternal nutritional status, state of ill health during pregnancy, the incidence of various complications in pregnancy, childbirth, and postpartum. Moreover, the availability and use of healthcare facilities, including prenatal and obstetric services, were also very affecting. So it is necessary to minimize the occurrence of maternal deaths. The government had made various efforts to reduce maternal mortality, but the results were still not optimal yet. If maternal mortality could be prevented as early as possible with appropriate identification, it could significantly reduce maternal mortality. The research aims to analyze the cause of maternal death in Tasikmalaya city in 2015. The research design used a quantitative approach in the form of observation. The population was all maternal deaths in Tasikmalaya City Health department in 2015. The study's affordable population was all maternal mortality data with a precise address and recorded in the OVM as many as 20 cases of death. Factors associated with maternal mortality were the problem relating to patients, health professionals, health infrastructure, and referrals. Moreover recording and reporting of maternal mortality also influenced the determination of proper diagnosis to decrease the number of maternal mortality. Maternal mortality was a problem that has never finished with the complexity of the cause. It requires efforts that involve many parties, not only the health authorities alone, but all stakeholders were supported by government regulation. This study could be the basis for further research on maternal mortality and can be used to enhance the knowledge of researchers, health professionals, and stakeholders about the factors that cause maternal deaths. This study's results are expected to know the causes of maternal mortality and used as guidelines in making policy to reduce maternal mortality.Keywords: Maternal mortality, related factors